DEVELOPING STUDENTS’ WORKSHEET USING SCIENTIFIC APPROACH IN TEACHING READING GRADE EIGHT STUDENTS OF SMP CERDAS MURNI TEMBUNG - Dwi Wulandari; Masitowarni Siregar (Universitas Negeri Medan, 2024)
This study concerns on how reading worksheet are developed for junior high school. This study was conducted by using Research and Development (R&D) design. It was started from collecting the data, analyzing data, designing course grid based on curriculum 2013, designing new reading worksheet, validating by experts, and revising for final product. The new students’ reading worksheet was designed based on scientific approach stages, which is contained of five stages; observing, questioning, experimenting, associating, and communicating. The source of data of this study was the grade VIII students of SMP Cerdas Murni Tembung consisting 26 students. Instrument of collecting data were questionnaire, and interview. After analyzing data, the researcher got the students’ need in learning English. The interview and questionnaire result proved that the students need students’ reading worksheet which contains for grade VIII. The materials which were developed were focused on descriptive text, recount text, and narrative text. The product had been validated by the experts. The average scores are 3,8 from English subject teacher and 3,4 from English lecturer. It means the developing students’ reading worksheet categorized as relevant for students of grade VIII.